Study on the willingness to enroll in the urban and rural residents basic medical insurance: from the perspectives of policy awareness and institutional trust - Yu, Qunjun; He, Ya; Li, Luyan; Xu, Danni; Li, Yalin; Yin, Qin; Lu, Ye; He, Mei; Ma, Sha (Frontiers in Public Health, 2025)
BackgroundAchieving universal health coverage remains a global health priority. Understanding factors that influence individuals' willingness to enroll in basic medical insurance is essential for system sustainability.ObjectivesThis study aims to examine the impact of policy awareness and institutional trust on the willingness of urban and rural residents to enroll in the Urban and Rural Residents Basic Medical Insurance (URRBMI), with implications for policy refinement. The goal is to improve the precision of policy implementation and encourage broader insurance enrollment, supporting system sustainability.MethodsA survey of 563 residents was conducted in a county of Yunnan Province, China. Descriptive analysis of respondent demographics was followed by multiple linear regression, using policy awareness, policy expectation and institutional trust as independent variables, and demographics as control variables, to identify significant factors affecting enrollment willingness.ResultsThe results of the survey showed that 87.4% of respondents were enrolled in the URRBMI. The regression model, with an adjusted R2 of 0.322, showed policy awareness (coefficient = 0.243, P < 0.001) and institutional trust (coefficient = 0.354, P < 0.001) significantly and positively influenced enrollment willingness. Age and annual household income were also significant factors.ConclusionPolicy awareness and institutional trust are key determinants of enrollment willingness, with age and income playing roles. Policy education and communication should be refined, leveraging big data for targeted outreach and flexible payment options to enhance enrollment and system sustainability.